The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a. (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

Santa Lucia superiore (Toirano, Ligurie) : reconstitution locale de la végétation ligure durant le Pléniglaciaire ancien - Kaniewski, David; Renault-Miskovsky, Josette; Tozzi, Carlo; de Lumley, Henry (Geobios, 2005)
Pollen analysis of Santa Lucia superiore cave (Italy) reports at local scale the lowland Ligurian vegetation during the Lower Pleniglacial (75 to 57 Kyr BP). The pollen proﬁle shows two AP extensions during a steppe-landscape episode in Liguria. The dry and cold phases caused the establishment of a steppe-landscape (NAP 92%) with Artemisia, Ephedra, Poaceae and Chenopodiaceae, similar to those mentioned in the Latium during the Pleniglacial. The increase of moisture generated a ﬁrst arboreal extension (Pinus, Betula, Corylus, Ulmus), which engendered the formation of an open-forest landscape (AP 43%). The second arboreal extension (AP 55%) was due to an increase of moisture and higher temperatures, which allowed the development of Mediterranean trees and shrubs (Quercus ilex, Olea, Phillyrea). This warming up occurred probably simultaneously with a secondary transgression during the glacial sea-level change. The upper part of the proﬁle shows an open vegetation, which indicates the return of a steppe-landscape. Pollen data, replaced in the multidisciplinary studies of the site, are well correlated with the fauna and sediment data.
Keywords: Full glacial; Liguria; Middle Palaeolithic; palynology; Prehistory; Upper Pleistocene

Madonna dell'Arma (San Remo, Italie) : expression locale de la végétation ligure au cours du Paléolithique moyen - Kaniewski, David; Renault-Miskovsky, Josette; de Lumley, Henry (Geobios, 2004)
Pollen analysis of Madonna dell’Arma cave inside part (Liguria, Italy) allowed us to reconstitute, at local scale, the Ligurian coastal vegetation between the end of the last interglacial period and the beginning of the pleniglacial. This transition period shows an important representation of arboreal cover and a persistence of thermophilous elements that allowed us to considerate the western Liguria as a periglacial refuge. During the end of the last interglacial, xerophytic, halophytic herbs and shrubs taken over from a Mediterranean pre-forest unit in the ﬁrst slopes constituted the coastal zone. The nearness ofArgentina torrent and theArmea inﬂuenced, in the coast, the existence of marshy zones colonized by hygrophilous trees. In the Ligurian lowlands spread out sclerophyllous and mesophilous forests according to altitude. The beginning of the pleniglacial is indicated in the sequence by increases of Pinus, Cupressaceae and Artemisia in the context of a decline in the thermophilous components. This picture of vegetation has become integrated into the multidisciplinary studies of the site and contributed to the elaboration of palaeoclimatic hypothesis similar as those revealed by the fauna.
Keywords: Interglacial; Liguria; Middle Palaeolithic; palynology; Pleniglacial; Prehistory; Upper Pleistocene